The effect of internet embeddedness on women’s non-farm employment under the power perception perspective: evidence from rural China - Yu, Song; Yang, Lulu; Yang, Shimei; Li, Lianjun (Frontiers in Psychology, 2024)
Introduction Female empowerment can promote gender equality and realize women’s comprehensive development, while the Internet has opened up an effective channel for female empowerment. Methods Given the relative lack of women’s rights in rural China and the rapid Internet development, this paper, based on the 2021 China Comprehensive Social Survey data, first analyses the effect of Internet embeddedness on rural women’s non-farm employment using the Probit model. Then, it uses the mediation effect model to explore the role of women’s rights perception in the mechanism between Internet embeddedness and women’s non-farm employment. Finally, based on age and regional differences, we also analyze the impact of Internet embeddedness on female non-farm employment. Results The paper draws the following conclusions: (1) Internet embedding can promote female non-farm employment, and the probability of female non-farm employment is 3.71% for each degree of Internet embedding. (2) Internet embedding can enhance women’s perception of their rights and thus promote women’s non-farm employment. (3) Internet embedding can enhance the perception of rights of young rural women, which can promote their nonfarm employment. However, the influence of internet embedding on middle-aged women’s perception of rights is not significant. (4) Internet embedding in the eastern region can enhance women’s perception of rights and realize women’s non-farm employment; on the contrary, in the central and western regions, Internet embedding cannot enhance rural women’s perception of rights. Discussion Therefore, this paper proposes to release further the impact of the Internet in promoting rural women’s non-farm employment to improve the deprivation of rural women’s rights and promote gender equality and women’s comprehensive development.